Стратегічне управління якістю продукції хлібопекарських підприємств - Малюк, С.О. (Культура народов Причерноморья, 2014)
У статті розглянуто поняття «якості продукції» як узагальненого комплексного поняття та економічної категорії. Досліджено стандарти Міжнародної організації по стандартизації ISO серії 9000, а також «петлю якості» як методичну основу управління нею. Розглянута система «тотального управління якістю» та її складові елементи. Визначені основні фактори впливу на формування якості хлібопекарської продукції та взаємозв’язок між ними. Запропоновані шляхи підвищення ефективності управління якістю за рахунок системного впливу на фактори формування якості продукції. В статье рассмотрено понятие «качества продукции» как обобщенного комплексного понятия и экономической категории. Исследованы стандарты Международной организации по стандартизации ISO серии 9000, а также «петля качества» как методическая основа управления им. Рассмотрена система «тотального управления качеством» и ее составляющие элементы. Опредлены основные факторы влияния на формирование качества хлебопекарной продукции и взаимосвязь между ними. Предложены пути повышения эффективности управления качеством за счет системного влияния на факторы формирования качества продукции. The article deals with the concept of «product quality» as a generalized complex economic concepts and categories. Proposed to examine the quality in terms of both producer and consumer. Accordingly, for manufacturers high quality products will be free from defects, which would prevent the sale. For consumers important are exactly those properties of products that meet their expectations. Studied the standards of the International Organization for Standardization ISO 9000, which established a single, recognized worldwide approach to the contractual terms of the assessment of quality systems and simultaneously regulate the relationship between producers and consumers. Methodical bases recognized quality management «as a loop», which is a common conceptual model of interdependent activities that affect the quality at various stages of definition needs to assess their satisfaction. Considered the system of «total quality management» and its components. The main factors influencing the formation of bakery products quality and the relationship between them. Suggested ways to improve the effectiveness of the quality management through system effect on factors of production quality. In particular, suggested the ways of improving the quality of raw materials, production modernization and improvement of measures to strengthen the material and technical base of production.